Analisis Teknis-Ekonomi Pembangkit Listrik Tenaga Hybrid Solar PV/Biogas off Grid System - R. Reski Eka Putra; Susi Afriani; Nanda Putri Miefthawati; Marhama Jelita (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
ABSTRACTReliability of the electric power system and fulfil the certification of sustainable industries in the palm oil industry are offered by utilizing the potential of renewable energy sources as power plants. This research is aimed to analyze the technical and economic aspects of the Solar PV-Biogas power plant at PT. TBS. The method used in this research is hybrid parallel with the off grid network system. In manual calculations showed an optimal generating system consisting of an anaerobic digester with a lagoon capacity of 28,934.81 m3, 1,560 kW biogas generator, 4,040.22 kWp PV array, 2000 kW bidirectional inverter, and 10,125 units of batteries with capacity of 1,547Ah. Then the system is evaluated using HOMER Pro software with project lifetime of 20 years, and the total electricity production obtained during the life of the project is able to supply loads continuously with an average excess electricity about 25.23%/years of total production. Meanwhile, in the economic analysis of hybrid power plants require an initial investment (NPC) of Rp.233,553,169,589.30, with total CO2 emissions of POME 44,073.75 tons/year, then the cost of Certified Emission Reduction is obtained about Rp.6,611,062,500/year. The calculation of economic feasibility results in a Net Present Value of Rp.136.266.578.753, Payback Period of 13,8 years, and an Internal Rate of Return of 9,41%. Based on the result of techno-economic analysis in the research, it can be concluded that this hybrid generating system has the potential to be developed for study that is more detailed if it is to be implemented.Keywords: HOMER Pro, Off-grid, PT. TBS, Solar PV/Biogas, Techno-economic.